ANALISIS KETERKAITAN IMPLEMENTASI REFORMASI BIROKRASI ANTAR WILAYAH DI JAWA TIMUR - Akhmad Amirudin; Amalia Rahmawati; Yahya Fahmi (PANGRIPTA, 2022)
Reform is an essential management effort expected to give good results in the system and structure. Effective reform of the information network of interpersonal communication. Most research has studied the structure and importance of public service delivery, but the interaction between network members. Yet the increased growth in public management has resulted in the growth of a network of actors operating in an interdependent manner, collectively producing public services. In addition, the experience of the reform process in several countries also reveals that employee reform is mainly influenced by the political interaction of bureaucrats and politics. This study aims to determine the relevance of 38 districts/cities in East Java in the urban reform index. The analytical method used is spatial autocorrelation. The analysis results show the relationship between several regions in East Java in the employee reform index. Namely Malang City and Sidoarjo Regency in 2018, Sampang Regency in 2018, and Situbondo Regency and Sampang Regency in 2020. The development of the implementation of Regency/City Government reforms in East Java in 2018-2022 continues to increase, although not yet. Therefore, efforts to increase the employee reform index must continue